Effects of tomato juices (Lycopersicum esculentum Mill) consumption on plasma lycopene levels of male light smokers (Faculty of Medicine Universitas Indonesia, 2004)
The study was an experimental study with pre- and post-test design, to evaluate the effects of tomato juices (Lycopersicum esculentum Mill) consumption on plasma lycopene level. Blood sample of 27 subjects with average age of 34.70 Â± 5.74 years old, moderate education level (85.2%), experienced direct contact with working environmental pollutant (40.74%) and smoked kretek cigarettes (77.78%) were given treatment with 350 gram/day of tomato juices (Lycopersicum esculentum Mill) which had been properly prepared for 4 consecutive days. The lycopene plasma level was examined before and after treatment. The findings showed that after treatment, the lycopene plasma level significantly increased. This showed that consumption of properly prepared of tomato juices will increase the lycopene plasma level. (Med J Indones 2004; 13: 146-50) Keywords: light smoker, tomato juices, lycopene plasma